Reshaping the world financial system – an imperative of sustainable development - CORBU, Ion (Annals of Spiru Haret University. Economic Series, 2016)
This paper presents the general and specific causes which led to the actual financial and economic crisis, the principal consequences of this crisis like some other theoretical considerations regarding the cyclical normal evolution of the economies and the major disequilibrium instauration between the market’s components which generates crisis. A critical analysis of the actual financial and monetary system emphasizes its pro-cyclic character. On the following pages, the weaknesses and vulnerabilities of the present system are put into light, starting with: lack of an international reserve currency to ensure stability and development, use of complex and opaque financial instruments, making decisions taking into account the rating agencies statistics which have serious problems especially in operating actions, unsecured procedures for the financial assets’ evaluation, existence of the so called “fiscal havens”, inefficiency of “the market’s invisible hand and aspects related to the current issues and sustainable development. Furthermore, the paper underlines the context of change and reform initiatives, governments’ concerns for re-building the financial and monetary actual system and, finally, action lines and intervention to change completely the system and introduce a new international reserve currency. The need of change, key word for the prevention of future crises and necessity in the context of sustainable development represents the basic conclusion of this work.